CORE STABILITY EXERCISE OUTWEIGHS SURYA NAMASKAR YOGA IN IMPROVING ABDOMINAL MUSCLE ENDURANCE AMONG STUDENTS OF YOGA AND HEALTH DEPARTMENT OF UHN I GUSTI BAGUS SUGRIWA DENPASAR - I Nyoman Subrata; I Nyoman Agus Pradnya Wiguna (Universitas Negeri Medan, 2022)
A reduced level of physical activity can cause a decline in core muscle endurance, one of which is abdominal muscle endurance. Abdominal muscle endurance plays a crucial role to support daily physical activity. Abdominal muscle endurance can be enhanced through physical exercises such as surya namaskar yoga and core stability exercise. This study aims to examine the difference in the effect of surya namaskar yoga and core stability exercise in improving abdominal muscle endurance among students of the yoga and health department at UHN I Gusti Bagus Sugriwa Denpasar. This study is an experimental study using a randomized pre- and post-test control group design. The subjects of this study were 12 students, which were divided into 2 groups. Group 1 received surya namaskar yoga and Group 2 received core stability exercise. Abdominal muscle endurance was measured using the flexor endurance muscle test. Based on the results of the independent t-test, there was a difference in the average abdominal muscle endurance after treatment between groups, with p-value = 0.008 (p <0.05), where the Mean of increase in abdominal muscle endurance in Group 1 was 20.16 ± 0.75, while in Group 2, it was 32.00 ± 2.09. Therefore, core stability exercise outweighs surya namaskar yoga in improving abdominal muscle endurance among students of yoga and health department of UHN I Gusti Bagus Sugriwa, Denpasar.